Strong-ties and weak-ties rationalities: toward a mental model of the consequences of kinship intensity - Yeh, Kuang-Hui; Terpstra Tong, Jane; Ting, Rachel Sing-Kiat; Bond, Michael Harris; Khosla, Meetu; Yadav, Virendra Pratap; Shukla, Shashwat; Liu, Charles; Sundararajan, Louise (Frontiers in Psychology, 2024)
There is growing evidence of the connection between variations in kinship intensity and cross-cultural differences in psychological traits. Contributing to this literature on kinship intensity, we put forward a mental model to explain the enduring connection between ancestral niche and psychological traits. Our model posits that two primary orientations or dispositions – strong-ties and weak-ties rationalities – have co-evolved with our ancestral niches to perpetuate– by internalizing and reproducing– the social structure (such as preferences for certain attitudes, values, and beliefs) of the ancestral niche. The findings from 1,291 participants across four societies - China, India, Taiwan, and the United States - support our hypothesis that strong-ties (weak-ties) rationalities, when activated, will endorse strong-tie (weak-ties) values and beliefs. This proposed model contributes to the toolbox of cultural and cross-cultural psychology in a twofold sense: First, in addition to the index of kinship intensity, it offers a measure of kin-based rationality as another predictor of psychological traits; second, it renders intelligible the niche and rationality disconnect prevalent in the globalizing era.